INDIKASI SOSIOLOGIS TERJADINYA POLIGAMI DI KALANGAN MASYARAKAT BOGOR - Mukhtar, Mukhtar; Amaliah, Nur (JURNAL ILMU SYARIAH, 2013)
Polygamy is one form of marriage is debated by the public, either supporting or were refused, they give a different argument. Sociologically, the act of polygamy is still viewed percussion by the people of Indonesia, including the area of Bogor, West Java. They are looking at someone who is polygamous are very powerful in economic matters, being able to feed the whole family, but others consider that polygamy is bad for hurting woman and unfaithful to his first wife. Variety perspective is then deemed necessary to do research on sociological indication of Bogor on polygamy.